2015
DOI: 10.1093/eurheartj/ehv435
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial evaluating everolimus-eluting Absorb bioresorbable scaffolds vs. everolimus-eluting metallic stents in patients with coronary artery disease: ABSORB Japan

Abstract: ClinicalTrials.gov, number NCT01844284.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
167
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 255 publications
(184 citation statements)
references
References 20 publications
5
167
3
9
Order By: Relevance
“…Recently, bioresorbable vascular scaffolds (BRS) were introduced, which provide temporary vessel scaffolding with drug delivery capacity but do not carry the limitations of a permanent metallic stent in the long term [8,9]. Prospective studies demonstrated BRS safety and efficacy on selected patients [10][11][12], but some studies have reported increased ST rates [13][14][15][16][17][18][19]. However, data on a large sample of ACS patients are still lacking [15,17,[20][21][22][23][24], and only few studies have evaluated the impact of lesion preparation and postdilatation of BRS [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioresorbable vascular scaffolds (BRS) were introduced, which provide temporary vessel scaffolding with drug delivery capacity but do not carry the limitations of a permanent metallic stent in the long term [8,9]. Prospective studies demonstrated BRS safety and efficacy on selected patients [10][11][12], but some studies have reported increased ST rates [13][14][15][16][17][18][19]. However, data on a large sample of ACS patients are still lacking [15,17,[20][21][22][23][24], and only few studies have evaluated the impact of lesion preparation and postdilatation of BRS [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The investigators reported a similar rate of stent thrombosis (1.5%) in both groups (89). In ABSORB China a total of 480 patients were randomized to be implanted with everolimus-eluting An interesting study compared BRS (ABSORB) with second-generation metal drug eluting stent in 100 complex lesions treated under OCT guidance (92).…”
Section: Clinical Trialsmentioning
confidence: 97%
“…Two interesting studies have reported recently: ABSORB Japan and ABSORB China (89,90). The studies were designed to enable approval of the BRS in Japan and China.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABSORB Japan used a wide non-inferiority margin for the difference in 1-year TLF (8.6%), based on an agreement with the Japanese Pharmaceutical and Medical Device Agency, which resulted in a small sample size (N=400). The trial showed a 0.4% risk difference in 1-year TLF between BVSs and EESs (4.2% in the BVS group and 3.8% in the EES group), and the upper bound of the confidence interval was 4.0% (8). The sample size of Absorb Japan was sufficient to power a test of non-inferiority for late lumen loss at 13 months, using a 0.20 mm non-inferiority margin, which ultimately showed a difference of 0.01 mm (0.13±0.30 mm in the BVS group and 0.12±0.32 mm in the EES group), with a 0.06 mm upper bound of the 95% confidence interval.…”
mentioning
confidence: 93%